Marine Spatial Planning in the Benguela Current Large Marine Ecosystem - Finke, Gunnar (2020)
The Benguela Current Large Marine Ecosystem (BCLME) in the south-east Atlantic covers the territorial waters and Exclusive Economic Zones (EEZ's) of Angola and Namibia and partly of South Africa. Increasing demands, user-user and user-environment conflicts occur throughout the area. The three countries, which are parties to the Benguela Current Convention (BCC), have begun to implement Marine Spatial Planning (MSP) to support the sustainable development of the area and enhance ocean governance. This makes the region one of the first in a developing economies context and on the African continent to introduce MSP. The article (1) traces the origin of MSP in the region and describes the reasons for its development, (2) reviews the status of MSP processes to date at the regional and national level, and (3) reflects on the regional and individual country processes in terms of differences and similarities in approach and process governance, shared opportunities and difficulties. The study finds that MSP in the region is introduced because of both strong interests to use it as a means to help grow the blue/ocean economy and as a mechanism to further the implementation of the ecosystem approach. Similar steps have been taken so far and alike approaches to MSP exist across the three countries, with the BCC as regional convention facilitating knowledge sharing and assisting to improve cross-border coherence and consistency on MSP from the outset. Although challenges, such as limited finances and data gaps exist both at national and regional level, the MSP processes to-date have created an enabling environment to develop the first marine spatial plans in each country and to exchange knowledge and experiences within the region and with other regions.